2012
DOI: 10.1111/j.1365-2621.2012.03014.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cold chain interruptions on the shelf life of fresh pork and poultry

Abstract: Summary In this study, the influence of fluctuations of the cold chain on the growth of Pseudomonas spp. on fresh pork and poultry and, therefore, their shelf life was evaluated. Thus, four storage trials were examined. In each trial, shelf life at the control scenario (4 °C, constant) was compared with shelf life at two dynamic scenarios including temperature shifts from 4 to 7 and to 15 °C, respectively. Overall, fresh pork and fresh poultry showed similar spoilage patterns at dynamic temperature conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
29
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 32 publications
6
29
0
1
Order By: Relevance
“…This shelf-life was even shorter than the shelf-life of shrimps stored at a higher constant temperature (15°C) (43 h) although they contained similar initial microbial concentrations. A similar observation was reported by Bruckner et al (2012), who found a remarkable shelf-life reduction of fresh pork and poultry due to temperature abuse in the beginning of storage. Our study highlighted the necessity of cooling shrimps as soon as they are caught.…”
Section: Tablesupporting
confidence: 77%
“…This shelf-life was even shorter than the shelf-life of shrimps stored at a higher constant temperature (15°C) (43 h) although they contained similar initial microbial concentrations. A similar observation was reported by Bruckner et al (2012), who found a remarkable shelf-life reduction of fresh pork and poultry due to temperature abuse in the beginning of storage. Our study highlighted the necessity of cooling shrimps as soon as they are caught.…”
Section: Tablesupporting
confidence: 77%
“…); however, other authors have set it at 1·8 (Bruckner et al . ). One reason for the difference in SI could be explained by the presence of different species of TVC with different metabolic activities and sensorial quality deterioration depending on the type of fresh product (Jacxsens et al .…”
Section: Discussionmentioning
confidence: 97%
“…This confirms the applicability of TVC as freshness indicator during the storage period (Bruckner et al . ). Treatments caused a significant increase ( P < 0·05) in pH of samples compared with the untreated (control) samples at the end of the storage period.…”
Section: Discussionmentioning
confidence: 97%
“…However, despite the wide biodiversity of microorganisms, the spoilage process of all proteinaceous foods is similar and it is caused by 1 predominant group, termed the specific spoilage organism (SSO) (Dalgaard ). The most commonly reported SSO species for aerobically stored pork and poultry meat are Pseudomonas , Shewanella or Brochothrix (Russell and others ; Nychas and others ; Bruckner and others ). Quality of meat and its spoilage are usually accessed by a subjective evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…Quality of meat and its spoilage are usually accessed by a subjective evaluation. Traditionally, the shelf life of raw meat is predicted based on minimal spoilage level of total viable count (TVC) (Huis in't Veld ; Bruckner and others ). However, the meat spoilage is commonly manifested as off‐odors and discoloration caused by the presence of volatile and non‐volatile compounds produced as a result of bacterial metabolism (Borch and others ).…”
Section: Introductionmentioning
confidence: 99%